New Herz Type Besov and Triebel-Lizorkin Spaces with Variable Exponents - Baohua Dong; Jingshi Xu (Journal of Function Spaces and Applications)
The authors establish the boundedness of vector-valued Hardy-Littlewood maximal operator in Herz spaces with variable exponents. Then new Herz type Besov and Triebel-Lizorkin spaces with variable exponents are introduced. Finally, characterizations of these new spaces by maximal functions are given.